Pengebangan Nuklir Iran dan Diplomasi Kepada IAEA - Hikmatul Akbar; Pinilih Kodimerinda (Jurnal Paradigma, 2012)
Iran considered as one of nuclear country since they have an advanced nuclear technology. With geographical position closed to Israel whose friend of United States (US). Iran becomes a threat to those states. Claiming the nuclear technology is only for peaceful purpose; Iran continues the development of nuclear technology. They allowed staff from International Atomic Energy Agency (IAEA) to check all the nuclear facilities in the country. Meanwhile, United States continue to accuse Iran of having nuclear weapon or facilities to build it. Using their power, US succeed to ask United Nation to push economic sanction against Iran. Resolutions were made to push Iran to stop nuclear program. In the other side, Iran persisting on using nuclear energy, since it has so many advantages compare to oil based energy.